2004
DOI: 10.1161/01.cir.0000147610.41984.e8
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Myocardial Estrogen Receptors in Human Aortic Stenosis

Abstract: Background-Estrogen receptor (ER)-mediated effects have been associated with the modulation of myocardial hypertrophy in animal models and in humans, but ER expression in the human heart and its relation to hypertrophymediated gene expression have not yet been analyzed. We therefore investigated sex-and disease-dependent alterations of myocardial ER expression in human aortic stenosis together with the expression of hypertrophy-related genes. Methods and Results-ER-␣ and -␤, calcineurin A-␤, and brain natriure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
81
1
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(93 citation statements)
references
References 24 publications
8
81
1
3
Order By: Relevance
“…23 An upregulation of ERa at both mRNA and protein level was associated with human aortic stenosis and with the end-stage human heart failure due to dilated cardiomyopathy. 21 In both cases, ERa was expressed at a comparable concentration in women and in men, and the increase in ERa occurred in both. 22 We demonstrated that the expression of ERs in human atrial slices was not changed following 24 h exposure to E2 treatment.…”
Section: Discussionmentioning
confidence: 84%
“…23 An upregulation of ERa at both mRNA and protein level was associated with human aortic stenosis and with the end-stage human heart failure due to dilated cardiomyopathy. 21 In both cases, ERa was expressed at a comparable concentration in women and in men, and the increase in ERa occurred in both. 22 We demonstrated that the expression of ERs in human atrial slices was not changed following 24 h exposure to E2 treatment.…”
Section: Discussionmentioning
confidence: 84%
“…Testosterone circulates at concentrations that are an order of magnitude greater than those of E 2 in the blood of postmenopausal women (Simpson 2002). In addition, androgen receptors are expressed in female hearts (Nordmeyer et al 2004, Lizotte et al 2009). An implication of the above is that androgens have an important role in the higher risk of CVD in postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 In contrast to previous studies, which failed to detect measurable amounts of ER␣ and ER␤ protein in the mouse heart, several independent studies reported on robust cardiac expression levels of both ER subtypes in rats and humans. 10,31,32 However, cardiac expression levels of ER␣ and ER␤ may not only vary between different species but also among young and senescent SHRs. Therefore, it is interesting to note that cardiac ER␣ expression was significantly lower in sham-operated and ovariectomized aged rats, whereas ER␤ was detected at comparable amounts in the heart of young and senescent rats.…”
Section: Discussionmentioning
confidence: 99%